Ultrasonic chemical sensor with organic monomolecular layer - Balcerzak, Andrzej; Rejmund, Feliks; Gutkiewicz, Piotr; Zienkiewicz, Bogusław; Zhavnerko, G. (Archives of Acoustics, 2006)
In this work a structure of a ultrasonic chemical sensor with organic monomolecular layer as well as introductory measurement with the help of a set-up constructed in IFTR PAS are presented. Chemical composition of this layer is an equimolar mixture of 5-[[1,3-dioxo-3- [4- (1-oxooctadecyl) phenyl] propyl] amino] – 1,3 – benzenedicarboxylic acid (DA) and cetylamine (CA). The thickness of this layer is equal to dimension of one molecule. The sensor layer was deposited on one channel of the bi-channel sensor delay line (made from lithium niobiate) by means of the Langmuir–Blodgett method. The chemical sensitivity of this sensor to some mixtures of air with vapor of volatile organic compounds has been investigated.